2023
DOI: 10.1038/s41746-023-00801-2
|View full text |Cite
|
Sign up to set email alerts
|

High night-to-night variability in sleep apnea severity is associated with uncontrolled hypertension

Abstract: Obstructive sleep apnea (OSA) severity can vary markedly from night-to-night. However, the impact of night-to-night variability in OSA severity on key cardiovascular outcomes such as hypertension is unknown. Thus, the primary aim of this study is to determine the effects of night-to-night variability in OSA severity on hypertension likelihood. This study uses in-home monitoring of 15,526 adults with ~180 nights per participant with an under-mattress sleep sensor device, plus ~30 repeat blood pressure measures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Given that OSA is associated with major incidents, and in some cases fatalities, in the rail industry 32 , the increased costs associated with screening are likely to be offset by the potential to reduce risk of major incidents in train drivers. Management is also likely to improve the negative associations of OSA sickness absenteeism 33 , poorer quality of life 34 , hypertension 20 and poorer mental health 35 which are all costly to the individual, the workplace and the health system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that OSA is associated with major incidents, and in some cases fatalities, in the rail industry 32 , the increased costs associated with screening are likely to be offset by the potential to reduce risk of major incidents in train drivers. Management is also likely to improve the negative associations of OSA sickness absenteeism 33 , poorer quality of life 34 , hypertension 20 and poorer mental health 35 which are all costly to the individual, the workplace and the health system.…”
Section: Discussionmentioning
confidence: 99%
“…Also of relevance, night-to-night variability in OSA severity can be significant, leading to misclassification of disease severity and misdiagnosis in 20–50% of cases when diagnosis is made using single-night PSG 42 , 43 . Multi-night assessment of OSA severity using low-cost ‘nearable’ sleep measurement devices has been shown to provide more reliable estimates of OSA severity and associated health outcomes compared to traditional PSG 20 , 44 . Using similar approaches for this worker population may facilitate more detailed analysis of the application of the Standard, and any future amendments or iterations, relative to OSA status in train drivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also allow investigation into the night-to-night variation in sleep and vital signs and how this variation associates with health outcomes and daytime function. Such approaches have already shown that night to night variation in sleep apnea associates with uncontrolled hypertension [57] and that night-to-night variation in sleep continuity associated with day-to-day variation in symptoms in people living with Alzheimer's [58].…”
Section: Discussionmentioning
confidence: 99%
“…The breathings disturbance detection has been performed using Emfit raw ballistography data in literature, but these algorithms are not open source or available directly from the manufacturer and hence not used in our analysis [55, 56]. The availability of these breathing disturbance estimates along with the acceptable agreement of the vital signs measures generated by the contactless technologies demonstrates their immediate potential usefulness in population wide deployment for home monitoring and care [57].…”
Section: Discussionmentioning
confidence: 99%